Use of Nonvascularized Autologous Fibular Strut Graft in the Treatment of Major Bone Defect after Periprosthetic Knee Fracture - Vincenzo Giordano; Bruno Parilha Coutinho; Mateus Kenji Miyahira; Felipe Serrão Mendes de Souza; Ney Pecegueiro do Amaral (Case Reports in Orthopedics)
We present the case of a patient who suffered a comminuted supracondylar periprosthetic femur fracture. The patient was an 86-year-old lady who suffered a minor fall at home and presented at our hospital with a right comminuted distal femur fracture around a total knee arthroplasty. The patient was submitted to a cruciate-sacrificing total knee replacement 6 years before at the same institution. Despite severe metaphyseal fragmentation and short distal fragment, the prosthesis was stable; thus, open fracture reduction and stabilization with internal fixation were performed. The surgical technique included the use of a nonvascularized autologous fibular strut graft as an augmentation technique in conjunction with double plating fixation. Clinically, patient presented a painless aligned knee 12 months after femur fixation, although she was not able to return to an independent level of activity. No pain involving the donor graft site was reported at the time of the most recent follow-up examination. This case study demonstrates the use of free nonvascularized autogenous fibular strut bone graft as an option to bridge major bone defects. This proved to be a relatively simple, not expensive procedure that can be done percutaneously and does not need high-quality training.